A Review on Investigations of the Mechanical and Microstructural Behaviour of Metal Matrix Composites Reinforced with Graphite and Silicon Carbide - M Divyansh; Dr. Vikas Gadpale; Mr. Abhinav Kumar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Nowadays composite materials are replacing conventional materials due to their high strength to weight ratio, biodegradable nature, and wear resistance. Aluminium metal matrix composites are gaining widespread acceptance for automobile, aerospace, agriculture farm machinery and many other industrial applications because of their essential properties such as high strength, low density, good wear resistance compared to any other metal. In the present study we deals with the addition of reinforcements such as graphite, fly ash, silicon carbide, red mud, organic material etc. to the aluminium matrix in various proportions. Each reinforced material has an individual property which when added improves the properties of the base alloy. Composite is prepared using liquid metal stir casting process.
Keywords: Aluminium Metal Matrix Composite; Liquid Metal Stir Casting Process; Composite; High Strength; Wear Resistance